The transformational CIO : leadership and innovation strategies for IT executives in a rapidly changing world - Muller, Hunter, 1960- (Hoboken, N.J. : Wiley, 2011)
"An actionable framework for leveraging technology to create business value, generate revenue, increase profits and improve customer relationships Describing in rich detail the actual processes, framework, and infrastructure required to develop and execute a strategy of continuous change and business transformation, The Transformational CIO focuses on four specific critical objectives where success is imperative. Includes real-world stories and revealing anecdotes from CIOs and IT thought leaders from companies such as Disney, Dell, Shell Oil, Kimberly-Clark, Kaiser Permanente, Computer Associates, Boston Scientific, salesforce.com, General Motors, Pitney Bowes, IBM, Intel, Microsoft, SAS, Procter & Gamble, Ogilvy Worldwide, Scholastic, Stryker, Navistar and the U.S. Tennis Association. Reveals how the modern CIO must become a master of transformation with the knowledge and ability to shift gears in a heartbeat. Considers critical objectives where success is imperative. In simple, straightforward language, The Transformational CIO is an invaluable toolkit enabling CIOs to stay ahead of the competition and seize the opportunities leading to professional success."--
Includes bibliographical references and index.
Keywords: Information technology -- Management -- Case studies; Chief information officers -- Case studies